Knowledge, beliefs, perceptions and barriers related to implementing smoke-free home practices in two rural settlement areas in Malaysia - Kamni, Siti Nurhasyimah Ayuni; Saiful Bahron, Nur Ain Nadhirah; Zulkifli, Aziemah; Uny, Isabelle; O’Donnell, Rachel; Prabandari, Yayi Suryo; Bintoro, Bagas Suryo; Zainal Abidin, Emilia; Semple, Sean (European Publishing, 2024)
INTRODUCTION Studies have found that parental smoking is the primary source of secondhand smoke (SHS) exposure among children, leading to respiratory illnesses, especially in non-smokers like children and women. Promoting a smoke-free home (SFH) is essential, especially among rural populations, and barriers or challenges to creating a SFH need to be better understood. This study aimed to determine the knowledge levels on SHS and to identify the beliefs, perceptions, barriers and facilitators of SFH practices among the rural population in Kuala Kubu Bharu, Selangor, Malaysia. METHODS This study employed a mixed-methods design, conducted in two rural settlement areas in 2022. Data were collected through surveys on SHS and SFH knowledge and face-to-face interviews using a topic guide. The quantitative data were analyzed using SPSS software while the qualitative data were analyzed using the thematic approach via NVivo 12. RESULTS Sixty participants completed the survey. Most of the respondents had a good (38%) or moderate (48%) knowledge level of SHS. No association was found between sociodemographic factors and knowledge level. Seven of the nine interviewees knew specific SHS-related health risks. Most participants believed that implementing SFH requires quitting or reducing smoking. Barriers to establishing a SFH included personal convenience, habits, attitudes, and social influence. Family encouragement, practicability, government, and quitting smoking were the facilitators for SFH. CONCLUSIONS These rural communities had moderate knowledge level of SHS and SFH. Men’s knowledge, beliefs and perceptions like associating SFH with quitting smoking may prevent SFH adoption. It is critical for the government and stakeholders to disseminate information and develop socially and culturally acceptable health promotion programs, incorporating the considerations from this study to increase the chances of SFH implementation in rural areas. © 2024 Zainal Abidin E. et al.